Antarctic Porifera homogenates as a source of enzymes and antibacterial substances: first results - Caruso G.; Papale M.; Azzaro M.; Rizzo C.; Lagana' P.; Caruso R.; Lo Giudice A. (Polar Biology, 2022)
Marine Porifera (sponges) are known to produce several bioactive metabolites having a biotechnological potential, mostly derived from their bacterial symbionts; however, current knowledge on the production of metabolites such as enzymes and antibacterial molecules in sponges living in Antarctic environments is not fully exhaustive and needs further deepened investigation. The interest in discovering the broad spectrum of natural products potentially derived from species adapted to colonize extreme environments stimulates the research toward Antarctic sponge bioprospection. In this study, whole homogenates of Antarctic Demospongiae, belonging to five different species [Haliclona (Rhizoniera) sp., Haliclona (Rhizoniera) dancoi, Microxina sarai, Dendrilla antarctica, and Mycale acerata] were collected from Terra Nova Bay (Ross Sea) and examined for presence and activity of enzymes, including lysozyme, and antibacterial substances. Enzyme activities (leucine aminopeptidase, beta-glucosidase, and alkaline phosphatase) were measured using fluorogenic substrates; lysozyme content was determined on plates containing lyophilized Micrococcus lysodeikticus cell walls as a substrate. Homogenates were screened in microtiter plates for their antibacterial activity against Antarctic bacterial isolates, and the absorbance reduction was measured with a microplate reader. All homogenates exhibited proteolytic, glycolytic, and phosphatasic activities, lysozyme and antibacterial activities at near “in situ” temperature (5 °C), with some differences among the examined species. Results confirmed that Antarctic sponge homogenates are interesting sources of different bioactive substances, likely produced from associated bacterial symbionts, and that could have great potential to be used in medicine or industrial applications.